Collagen hydrogel capable of logically releasing cerium oxide nanoparticles and iron oxide nanoparticles, preparation method and application
By loading the logical release mechanism of CEO2 and Fe2O3 nanoparticles in collagen hydrogel, the problem of the existing method of treating the existing osteoarthritis method is solved. Cangenia tissue regeneration and inflammation relief.
Patent Information
- Application Number
- CN202410523643.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-28
- Publication Date
- 2025-01-28
Smart Images

Figure CN119367591A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a collagen hydrogel capable of logically releasing cerium oxide nanoparticles and iron oxide nanoparticles, a preparation method and an application thereof. Background Art
[0002] Osteoarthritis (OA) is a common and disabling disease that affects the lives of hundreds of millions of people worldwide. According to statistics, the annual treatment cost for OA patients exceeds US$16.5 billion, which has caused tremendous economic pressure on both individual patients and the global healthcare system. At present, the clinical treatment methods for OA mainly include joint cavity perfusion, artificial joint replacement and autologous chondrocyte transplantation. Although these methods have achieved temporary success in clinical applications, they still have obvious disadvantages, such as high medical costs, loosening of prostheses and limited cell sources.
[0003] The repair process of OA includes several different but continuous physiological stages, mainly the inflammatory stage and the proliferation stage. Studies have found that the synergistic effect of these two stages can promote the reconstruction of articular cartilage. However, the nanoparticle composite hydrogels reported so far usually only focus on regulating a certain stage of OA repair, but ignore the continuity and synergy of different repair stages. For example, the invention patent CN116041967A discloses an injectable anti-inflammatory hydrogel for relieving osteoarthritis, which can effectively regulate the osteoarthritis microenvironment and protect cartilage, and mainly treat osteoarthritis from the anti-inflammatory aspect; the invention patent CN113999404B discloses a preparation method of a double-cross-linked stem cell sphere hydrogel for osteoarthritis, which has good mechanical properties, controllable degradation rate, is conducive to the survival of 3D cell spheres, can be long-lasting moisturizing, lubricating, and sustained release of biological factors, and mainly treats osteoarthritis from the aspect of cell proliferation. However, the above treatments are not carried out for different repair stages of osteoarthritis. Therefore, it is imperative to develop drugs for multi-stage systemic treatment of OA.
[0004] The inventor unexpectedly discovered that CeO2 nanoparticles, poly (D, L-lactic acid-co-glycolic acid) microspheres (pFe2O3) loaded with Fe2O3 nanoparticles, and thiol-modified collagen (Col-SH) can be cross-linked to form CSH-CeO2-pFe2O3 hydrogels with good mechanical strength and injectability. The hydrogel can sensitively respond to high concentrations of ROS, and the explosive release of CeO2 nanoparticles can effectively regulate abnormal reactions during the inflammatory phase, while the subsequent sustained release of Fe2O3 nanoparticles from the exposed polylactic acid-co-glycolic acid microspheres can significantly promote cartilage regeneration during the proliferation phase. In the rat osteoarticular cartilage defect model, the logical release of CeO2 and Fe2O3 nanoparticles gives CSH-CeO2-pFe2O3 hydrogels the dual functions of first anti-inflammatory and then repair, thereby significantly promoting cartilage tissue regeneration. Summary of the invention
[0005] In view of the above technical problems, the object of the present invention is to provide a collagen hydrogel that logically releases cerium oxide nanoparticles and iron oxide nanoparticles. The collagen hydrogel includes a collagen substrate, and cerium oxide nanoparticles and iron oxide nanoparticles uniformly cross-linked on the collagen substrate, and the iron oxide nanoparticles are loaded in poly (D, L-lactic acid-co-glycolic acid) microspheres.
[0006] Preferably, the collagen is animal type I collagen.
[0007] Preferably, the collagen is thiol-modified yak type I collagen.
[0008] Preferably, the contents of the components in the collagen hydrogel are as follows: 100 μL of 1 mM aqueous solution of cerium oxide nanoparticles, 5 mg of iron oxide nanoparticles and 900 μL of 5 mg / mL thiol-modified yak type I collagen.
[0009] The second object of the present invention is to provide a method for preparing the collagen hydrogel, wherein the method comprises the following steps:
[0010] (1) Weighing thiol-modified type I collagen and dissolving it in acetic acid solution, stirring to obtain a solution with a final concentration of 5 mg / mL;
[0011] (2) encapsulating the thiol-modified type I collagen solution obtained in step (1) into a dialysis bag and performing gradient dialysis until it becomes neutral;
[0012] (3) 100 μL of 1 mM cerium oxide nanoparticle aqueous solution, 5 mg of iron oxide nanoparticles and 900 μL of thiol-modified yak type I collagen solution were mixed and allowed to stand at room temperature to obtain CSH-CeO2-pFe2O3 hydrogel.
[0013] The third object of the present invention is to provide the use of the collagen hydrogel in promoting bone / cartilage tissue regeneration.
[0014] The fourth object of the present invention is to provide the use of the collagen hydrogel in the preparation of a drug for preventing and / or treating cartilage defects.
[0015] The fifth object of the present invention is to provide the use of the collagen hydrogel in the preparation of a drug for preventing and / or treating arthritis.
[0016] Preferably, the arthritis is infectious arthritis and / or non-infectious arthritis.
[0017] Preferably, the non-infectious arthritis includes one or more of degenerative arthritis, rheumatoid arthritis, rheumatic arthritis, gouty arthritis and osteoarthritis.
[0018] The beneficial effects of the present invention are as follows: (1) The present invention provides a collagen hydrogel that logically releases cerium oxide nanoparticles and iron oxide nanoparticles, wherein the collagen hydrogel comprises a collagen substrate, and cerium oxide nanoparticles and iron oxide nanoparticles uniformly cross-linked on the collagen substrate, wherein the iron oxide nanoparticles are loaded in poly (D, L-lactic acid-co-glycolic acid) microspheres; (2) The collagen hydrogel has good mechanical strength, injectability and significant self-healing ability; (3) The collagen hydrogel can intelligently respond to high levels of ROS and achieve explosive release of cerium oxide nanoparticles and delayed and sustained release of iron oxide nanoparticles; (4) The collagen hydrogel can also release cerium oxide nanoparticles and iron oxide nanoparticles in a continuous manner; The collagen hydrogel has significant resistance to enzyme degradation and sustained antioxidant effect; (5) The collagen hydrogel has excellent biocompatibility and bioactivity, is non-cytotoxic, and can significantly promote cell proliferation, adhesion, and chondrogenic differentiation of bone marrow mesenchymal stem cells; (6) The collagen hydrogel can effectively relieve inflammation, inhibit the pro-inflammatory (M1) phenotype of macrophages and promote their anti-inflammatory (M2) phenotype, while upregulating the expression of anti-inflammatory factors and downregulating the expression of pro-inflammatory factors; (7) The collagen hydrogel can accelerate the deposition of collagen fibers and the secretion of proteoglycans, thereby significantly promoting the regeneration of cartilage tissue; (8) The collagen hydrogel can be used in the clinical treatment of osteoarthritis. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Physical and chemical characterization of hydrogels Note: A is a photograph of Col-CeO2-pFe2O3, CSH-CeO2, CSH-pFe2O3 and CSH-CeO2-pFe2O3 hydrogels; B is the SEM image of Col-CeO2-pFe2O3, CSH-CeO2, CSH-pFe2O3 and CSH-CeO2-pFe2O3 hydrogels; C is the energy spectrum analysis of CSH-CeO2-pFe2O3 hydrogel.
[0020] Figure 2 Mechanical and injectable properties of hydrogels Note: A is the strain-dependent oscillatory shear rheology test of Col-CeO2-pFe2O3, CSH-CeO2, CSH-pFe2O3, and CSH-CeO2-pFe2O3 hydrogels;
[0021] B is the frequency-dependent oscillatory shear rheology test of Col-CeO2-pFe2O3, CSH-CeO2, CSH-pFe2O3 and CSH-CeO2-pFe2O3 hydrogels;
[0022] C is the continuous step strain test of Col-CeO2-pFe2O3, CSH-CeO2, CSH-pFe2O3 and CSH-CeO2-pFe2O3 hydrogels;
[0023] D is the injection performance test of CSH-CeO2-pFe2O3 hydrogel.
[0024] Figure 3 In vitro degradation and release behavior of hydrogels Note: A is the cumulative release of Col-CeO2-Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 hydrogels in PBS; B is a partial enlarged view of the cumulative release of CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 hydrogels in PBS;
[0025] C is the cumulative release of CSH-CeO2-pFe2O3 hydrogel in PBS, 0.1mM H2O2 and 0.5mM H2O2;
[0026] D is the enzymatic degradation characteristics of Col-CeO2-Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 hydrogels; E is the accumulation of CeO2 and Fe2O3 in the enzymatic degradation products of Col-CeO2-Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 hydrogels;
[0027] F is the DPPH scavenging effect of Col-CeO2-Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 hydrogels.
[0028] Figure 4 Cytotoxicity and proliferation
[0029] Note: A is the in vitro cytotoxicity of pFe2O3;
[0030] B is the in vitro cytotoxicity of CeO2;
[0031] C is the CCK-8 assay of bone marrow mesenchymal stem cells (BMSCs) co-cultured with CeO2, Fe2O3, CSH-CeO2-Fe2O3, and CSH-CeO2-pFe2O3;
[0032] D is the live / dead cell staining image of BMSCs co-cultured with CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3.
[0033] Figure 5Cell adhesion and chondrogenic differentiation Note: A is the immunofluorescence staining of BMSCs co-cultured with CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3;
[0034] B is the relative expression level of Acan gene in BMSCs co-cultured with CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3;
[0035] C is the relative expression of Col2a1 gene in BMSCs co-cultured with CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3;
[0036] D is the relative expression level of Sox9 gene in BMSCs co-cultured with CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3.
[0037] Figure 6 Anti-inflammatory effect Note: A is the live / dead cell staining of RAW264.7 cells co-cultured with CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3;
[0038] B is the relative expression of IL-10 gene in RAW264.7 cells in CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3;
[0039] C is the relative expression of IL-18 gene in RAW264.7 cells in CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3;
[0040] D is the relative expression of IL-1β gene in RAW264.7 cells in CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3;
[0041] E is the relative expression of TNF-α gene in RAW264.7 cells in CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3;
[0042] F is IL-1β antibody staining of RAW264.7 cells in CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3; G is CD86 antibody staining of RAW264.7 cells in CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3;
[0043] H is CD206 antibody staining of RAW264.7 cells in CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3.
[0044] Figure 7 Cartilage tissue regeneration after 4 and 8 weeks of implantation into the defect Note: A is the appearance graph of CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 groups;
[0045] B is the macrohistological scores of CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 groups;
[0046] C is the H&E tissue staining image of CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 groups;
[0047] D is the Masson tissue staining image of CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 groups; E is the Saf-O / FG tissue staining image of CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 groups. DETAILED DESCRIPTION
[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] It should be noted that the reagents used in the following examples, unless otherwise specified, can be purchased from the market.
[0050] In the following examples, it should be noted that CeO2 is the abbreviation of cerium oxide nanoparticles; Fe2O3 is the abbreviation of iron oxide nanoparticles; PLGA is the abbreviation of poly (D, L-lactic acid-co-glycolic acid); pFe2O3 is the abbreviation of poly (D, L-lactic acid-co-glycolic acid) microspheres encapsulating iron oxide nanoparticles; CSH-CeO2-pFe2O3 is the abbreviation of collagen hydrogel loaded with cerium oxide nanoparticles and poly (D, L-lactic acid-co-glycolic acid) microspheres encapsulating iron oxide nanoparticles; Col-SH is the abbreviation of thiol-modified type I collagen. In some examples and drawings of the specification, the abbreviations are directly used instead of the full names, which have the same meaning.
[0051] Example 1 Preparation of pFe2O3
[0052] A 50 mg / mL PLGA-dichloromethane solution and a 3 mg / mL Fe2O3 nanoparticle aqueous solution were fully emulsified using a homogenizer to form a single emulsion (W / O) with extremely high uniformity; the obtained single emulsion was added to 10 mL 0.5% (w / v) PVA aqueous solution and emulsified again to form a double emulsion (W / O / W); finally, the synthesized double emulsion was added to 200 mL 0.5% (w / v) PVA aqueous solution and continuously stirred to gradually evaporate the organic solvent; it was washed with ethanol and distilled water to finally form Fe2O3 nanoparticle-loaded poly (D, L-lactic acid-co-glycolic acid) microspheres (pFe2O3).
[0053] Example 2 Preparation of Col-SH
[0054] Yak type I collagen was dissolved in 50 mL of acetic acid to form a 1 mg / mL uniform solution, and the pH was adjusted to 8.0 with a NaOH solution; 0.2 M disodium hydrogen phosphate-sodium dihydrogen phosphate (PBS) buffer solution, as well as 2 mg EDTA and 40 mg DL-N-acetylhomocysteine thiolactone (AHCT) were added; under nitrogen protection, the mixture was stirred at room temperature for 24 hours, 200 mg dithiothreitol (DTT) was added, and stirring was continued for 12 hours; after dialysis and freeze-drying, thiol-modified type I collagen (Col-SH) was obtained.
[0055] Example 3 Preparation of CSH-CeO2-pFe2O3 Hydrogel
[0056] A certain amount of Col-SH was weighed and dissolved in 0.3M acetic acid solution, and stirred thoroughly to form a uniform solution with a concentration of 5mg / mL; the Col-SH solution was then encapsulated in a dialysis bag (8-14KDa) for gradient dialysis to achieve neutrality; subsequently, 100μL 1mM CeO2 aqueous solution, 5mgpFe2O3 and 900μL Col-SH solution were quickly and evenly mixed and allowed to stand at room temperature for 4 hours to oxidize and form CSH-CeO2-pFe2O3 hydrogel, as shown in FIG. Figure 1 As shown in A.
[0057] Example 4 Preparation of CSH-CeO2 hydrogel
[0058] A certain amount of Col-SH was weighed and dissolved in 0.3M acetic acid solution to form a uniform solution with a concentration of 5 mg / mL, and then it was made neutral by gradient dialysis; then, 100 μL of 1mM CeO2 aqueous solution was mixed with 900 μL of Col-SH solution and allowed to stand at room temperature for 4 hours to oxidize and form CSH-CeO2 hydrogel, such as Figure 1 As shown in A.
[0059] Example 5 Preparation of CSH-pFe2O3 Hydrogel
[0060] A certain amount of Col-SH was weighed and dissolved in 0.3 M acetic acid solution to form a uniform solution with a concentration of 5 mg / mL, and then it was made neutral by gradient dialysis; then, 5 mg pFe2O3 was mixed with 900 μL of Col-SH solution and allowed to stand at room temperature for 4 hours to oxidize and form CSH-pFe2O3 hydrogel, such as Figure 1 As shown in A.
[0061] Example 6 Preparation of CSH-CeO2-Fe2O3 Hydrogel
[0062] A certain amount of Col-SH was weighed and dissolved in 0.3M acetic acid solution to form a uniform solution with a concentration of 5 mg / mL, and then it was made neutral through gradient dialysis; then, 100μL of 1mM CeO2 aqueous solution, 0.15mg Fe2O3 and 900μL of Col-SH solution were mixed and left to stand at room temperature for 4 hours to oxidize and form CSH-CeO2-Fe2O3 hydrogel.
[0063] Example 7 Preparation of Col-CeO2-Fe2O3 Hydrogel
[0064] A certain amount of yak type I collagen was weighed and dissolved in 0.3M acetic acid solution to form a uniform solution with a concentration of 5 mg / mL, and then gradient dialysis was performed to make it neutral; then, 100 μL of 1mM CeO2 aqueous solution, 0.15mg Fe2O3 and 900 μL of yak type I collagen solution were mixed and allowed to stand at room temperature for 4 hours to finally obtain Col-CeO2-Fe2O3 hydrogel, such as Figure 1 As shown in A.
[0065] Example 8 Physicochemical Characterization of Hydrogel
[0066] (1) The CSH-CeO2-pFe2O3, CSH-CeO2, CSH-pFe2O3 and Col-CeO2-Fe2O3 hydrogels prepared in Examples 3, 4, 5 and 7 were freeze-dried and then fixed on a sample stage. After gold spraying for 25 seconds, the sample morphology was detected using a scanning electron microscope (SEM) at a voltage of 5.0 kV.
[0067] The results of scanning electron microscopy are as follows Figure 1B shows the SEM images of Col-CeO2-Fe2O3, CSH-CeO2, CSH-pFe2O3 and CSH-CeO2-pFe2O3 from left to right. The results show that the internal pore structure of Col-CeO2-Fe2O3 hydrogel is unevenly distributed; in contrast, CSH-CeO2, CSH-pFe2O3 and CSH-CeO2-pFe2O3 hydrogels present a highly ordered network structure, with average pore sizes of approximately 185.8±18.8μm, 137.5±13.6μm and 125.8±17.9μm, respectively.
[0068] (2) The CSH-CeO2-pFe2O3 hydrogel prepared in Example 3 was freeze-dried and then fixed on a sample stage. After gold spraying for 25 seconds, energy dispersive spectroscopy (EDS) was used to detect the element distribution in the sample at a voltage of 5.0 kV.
[0069] The results of energy dispersive spectroscopy are as follows Figure 1 As shown in Figure C, C, O, S, Ce and Fe elements are uniformly distributed in CSH-CeO2-pFe2O3 hydrogel. The results show that CSH-CeO2-pFe2O3 hydrogel contains collagen, CeO2 and Fe2O3, and the two nanoparticles are uniformly distributed.
[0070] Example 9 Mechanics and injectability of hydrogels
[0071] (1) CSH-CeO2-pFe2O3, CSH-CeO2, CSH-pFe2O3 and Col-CeO2-Fe2O3 hydrogels were prepared according to Examples 3, 4, 5 and 7, and their rheological behaviors as a function of strain were measured at a fixed frequency (1 Hz).
[0072] The results are as follows Figure 2 As shown in A, the critical strain values of Col-CeO2-Fe2O3, CSH-CeO2, CSH-pFe2O3 and CSH-CeO2-pFe2O3 hydrogels at the gel-sol transition point are approximately 74.6%, 55.6%, 45.8% and 37.4%, respectively. The results show that CSH-CeO2-pFe2O3 hydrogel has good viscoelasticity.
[0073] (2) The CSH-CeO2-pFe2O3, CSH-CeO2, CSH-pFe2O3 and Col-CeO2-Fe2O3 hydrogels prepared according to Examples 3, 4, 5 and 7 were then measured for their frequency-dependent rheological behaviors at a fixed strain (1%).
[0074] The results are as follows Figure 2As shown in Figure B, the G' values of Col-CeO2-Fe2O3, CSH-CeO2, CSH-pFe2O3 and CSH-CeO2-pFe2O3 hydrogels are dominant, which are approximately 60.8 Pa, 891.4 Pa, 921.0 Pa and 1582.2 Pa, respectively. The results show that the CSH-CeO2-pFe2O3 hydrogel has significantly increased mechanical strength.
[0075] (3) CSH-CeO2-pFe2O3, CSH-CeO2, CSH-pFe2O3 and Col-CeO2-Fe2O3 hydrogels were prepared according to Examples 3, 4, 5 and 7, and then dynamic step strain measurements were performed at a low strain of γ=1.0% and a high strain of γ=300%.
[0076] The results are as follows Figure 2 As shown in Figure C, at high strain (300%), the network structure of CSH-CeO2-pFe2O3, CSH-CeO2, CSH-pFe2O3 and Col-CeO2-Fe2O3 hydrogels was rapidly destroyed, and G' dropped sharply to about 1.5Pa, 74.6Pa, 84.6Pa and 94.1Pa; when adjusted to low strain (1%), G' and G" of all hydrogels were almost completely recovered in a short time. The results show that CSH-CeO2-pFe2O3 hydrogel has significant self-healing ability.
[0077] (4) CSH-CeO2-pFe2O3 hydrogel was prepared according to Example 3, and then placed in a 1 mL syringe and extruded into a glass culture dish.
[0078] The results are as follows Figure 2 As shown in Figure D, CSH-CeO2-pFe2O3 hydrogel can be uniformly and continuously extruded from the injection and can form recognizable patterns such as "Fe" and "Ce". The results show that CSH-CeO2-pFe2O3 hydrogel has good injectability.
[0079] Example 10 In vitro degradation and release behavior of hydrogel
[0080] (1) CSH-CeO2-pFe2O3, CSH-CeO2-Fe2O3 and Col-CeO2-Fe2O3 hydrogels were prepared according to Examples 3, 6 and 7, encapsulated in dialysis bags (8-10 KDa), immersed in PBS solutions with a volume ratio of 1:20, and incubated in an oscillator at 37°C. At each time point, the concentration of CeO2 and Fe2O3 nanoparticles released in the solution was measured using a UV-visible photometer.
[0081] The results are as follows Figure 3As shown in AB, the CeO2 and Fe2O3 nanoparticles in Col-CeO2-Fe2O3 hydrogel were almost completely released within 5 days, while the CeO2 and Fe2O3 nanoparticles in CSH-CeO2-Fe2O3 showed an S-shaped curve release, with a release rate of 96.5% and 83.7% within 20 days. Compared with CSH-CeO2-Fe2O3 hydrogel, the release rate of Fe2O3 nanoparticles in CSH-CeO2-pFe2O3 hydrogel was significantly slower, with only 11.6% released after 7 days, while the release of Fe2O3 nanoparticles in CSH-CeO2-Fe2O3 hydrogel was as high as 73.6%. The results show that CSH-CeO2-pFe2O3 hydrogel can achieve the sequential release of CeO2 and Fe2O3 nanoparticles.
[0082] (2) CSH-CeO2-pFe2O3 hydrogel was prepared according to Example 3, and encapsulated with dialysis bags (8-10 KDa), and immersed in PBS solution, 0.1 mM H2O2 and 0.5 mM H2O2 solution, respectively. At each time point, the release of CeO2 nanoparticles from CSH-CeO2-pFe2O3 hydrogel was evaluated using a UV-visible spectrophotometer.
[0083] The results are as follows Figure 3 As shown in Figure C, the release of CeO2 nanoparticles increased with the increase of H2O2 concentration. After 48 hours, the release rates of CeO2 nanoparticles in PBS solution, 0.1mM H2O2 and 0.5mM H2O2 solution were 41.3%, 74.9% and 90.6%, respectively. The results show that CSH-CeO2-pFe2O3 hydrogel can intelligently respond to ROS and achieve controllable release of CeO2 nanoparticles.
[0084] (3) The CSH-CeO2-pFe2O3, CSH-CeO2-Fe2O3 and Col-CeO2-Fe2O3 hydrogels prepared in Examples 3, 6 and 7 were freeze-dried and accurately weighed (m0, mg), and treated with a collagenase solution with a concentration of 10 U / mL at 37°C. At specific time points, the samples were removed from the collagenase solution and rinsed three times with deionized water. After freeze-drying, the remaining samples were weighed again (m t The calculation formula of the mass degradation percentage (MD, %) of the sample is: MD (%) = (m0-m t ) / m0×100%.
[0085] The results are as follows Figure 3As shown in D, Col-CeO2-Fe2O3 reached enzyme degradation equilibrium within only 48 hours, with a degradation rate of 93.8%. In contrast, the degradation rate of CSH-CeO2-Fe2O3 was only 55.2% after 2 days, and it reached enzyme degradation equilibrium after 12 days, with a degradation rate of 91.7%. The degradation rate of CSH-CeO2-pFe2O3 hydrogel was relatively low, only 44.2% after 14 days. The results show that CSH-CeO2-pFe2O3 hydrogel has significant resistance to enzyme degradation.
[0086] (4) The CSH-CeO2-pFe2O3, CSH-CeO2-Fe2O3 and Col-CeO2-Fe2O3 hydrogels prepared in Examples 3, 6 and 7 were freeze-dried and treated with a collagenase solution having a concentration of 10 U / mL at 37° C. At specific time points, samples were taken from the collagenase solution, and the degradation products in the solution were analyzed using a UV spectrophotometer.
[0087] The results are as follows Figure 3 As shown in E, the concentration of CeO2 and Fe2O3 nanoparticles in the degradation products of CSH-CeO2-pFe2O3 gradually increased with time. The results showed that CeO2 and Fe2O3 nanoparticles were continuously released from CSH-CeO2-pFe2O3 hydrogel.
[0088] (5) The CSH-CeO2-pFe2O3, CSH-CeO2-Fe2O3 and Col-CeO2-Fe2O3 hydrogels prepared in Examples 3, 6 and 7 were encapsulated in dialysis bags (8-10 KDa) and immersed in PBS solution. At different time points, 10 μL of the hydrogel extract was mixed with 1,1-diphenyl-2-picrylhydrazyl (DPPH) ethanol solution and incubated for 30 minutes in dark conditions. The absorbance was measured at a wavelength of 515 nm using an ultraviolet spectrophotometer.
[0089] The results are as follows Figure 3 As shown in Figure F, on the first day, the free radical scavenging rate of the Col-CeO2-Fe2O3 hydrogel extract reached 22.3%, which was significantly higher than that of CSH-CeO2-Fe2O3 hydrogel (13.7%) and CSH-CeO2-pFe2O3 hydrogel (14.5%); on the seventh day, the free radical scavenging efficiency of the CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 hydrogel extracts was significantly higher than that of Col-CeO2-Fe2O3 hydrogel. These results indicate that CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 hydrogels have sustained antioxidant effects.
[0090] Example 11 Cytotoxicity and Proliferation
[0091] (1) The adherent BMSCs were digested with trypsin and diluted with α-MEM complete medium to a density of 2×10 5 cells / mL of cell suspension. 100 μL of BMSCs suspension containing different concentrations of pFe2O3 was added to each well of a 96-well plate and cultured in an incubator for 24 hours. The culture medium was removed and 100 μL of 10% CCK-8 solution was added to each well. After culturing at 37°C for 1 hour, the absorbance at 450 nm was measured using a microplate reader.
[0092] The results are as follows Figure 4 As shown in A, when pFe2O3 was co-cultured with cells in a concentration gradient range of 0.1 to 10 mg / mL, the cell viability of BMSCs was always close to 100%. The results showed that pFe2O3 had no cytotoxicity.
[0093] (2) The adherent BMSCs were digested with trypsin and diluted with α-MEM complete medium to a density of 2×10 5 cells / mL of cell suspension. 100 μL of BMSCs suspension containing different concentrations of CeO2 was added to each well of a 96-well plate and cultured in an incubator for 24 hours. The culture medium was removed and 100 μL of 10% CCK-8 solution was added to each well. After culturing at 37°C for 1 hour, the absorbance at 450 nm was measured using a microplate reader.
[0094] The results are as follows Figure 4 As shown in Figure B, when the concentration of CeO2 nanoparticles is lower than 0.5 mM, the co-cultured BMSCs can still maintain a high cell viability. The results show that low concentrations of CeO2 nanoparticles have no cytotoxicity.
[0095] (3) 100 μL of cell suspension containing CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 was added to a 96-well plate and cultured for 1, 7 and 14 days, respectively. The culture medium was removed and 100 μL of 10% CCK-8 solution was added to each well. After incubation at 37°C for 1 hour, the absorbance at 450 nm was measured using a microplate reader.
[0096] The results are as follows Figure 4As shown in Figure C, the cell viability of the CeO2, Fe2O3, CSH-CeO2-Fe2O3, and CSH-CeO2-pFe2O3 groups increased in a time-dependent manner from 1 to 14 days. The number of cells in the CSH-CeO2-pFe2O3 group increased significantly on day 14 compared with the blank, CeO2, Fe2O3, and CSH-CeO2-Fe2O3 groups. These results indicate that the CSH-CeO2-pFe2O3 hydrogel can continuously promote cell proliferation over a long period of time.
[0097] (4) CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 were mixed with BMSCs cells to form a density of 1×10 5 cells / mL suspension. Subsequently, they were added to laser confocal culture dishes and cultured for 7 and 14 days. At each time point, calcein-AM and propidium iodide were used to stain the viable and dead cells, respectively. Laser confocal microscopy was used to collect images.
[0098] The results are as follows Figure 4 As shown in D, after 14 days of culture, the proportion of surviving cells in CSH-CeO2-pFe2O3 hydrogel was significantly the highest. The results showed that CSH-CeO2-pFe2O3 hydrogel can significantly enhance the proliferation ability of BMSCs over a long period of time by controlling the sustained release of Fe2O3 nanoparticles.
[0099] Example 12 Cell Adhesion and Chondrogenic Differentiation
[0100] (1) 1 mL of cell suspension containing CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 was added to a laser confocal microplate, and after culturing in an incubator for 5 days, BMSCs were fixed with 4% paraformaldehyde for 15 minutes, permeabilized with 0.1% Triton X-100 for 5 minutes, blocked with 1% BSA solution at room temperature for 30 minutes, and stained with phosphatidylcholine-tetramethylrhodamine isothiocyanate and Hoechst 33342. Finally, fluorescence images were obtained using a laser confocal microscope.
[0101] The results are as follows Figure 5 As shown in A, the cells in the blank group and CeO2 group were slender and contained a large number of F-actin fibers in the cytoplasm; in contrast, a large number of spindle-shaped cells with complete cytoskeleton structures were observed in the Fe2O3 group and CSH-CeO2-Fe2O3 group; the CSH-CeO2-Fe2O3 group contained more spindle-shaped cells with exquisite actin cytoskeleton structures. The results showed that CSH-CeO2-Fe2O3 hydrogel can effectively promote the adhesion of BMSCs.
[0102] (2) BMSCs were mixed with CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 to form a 3D-hybrid composite with a density of 1×10 5 cells / mL suspension, and incubated in 6-well plates for 7 and 14 days, respectively. Total RNA was extracted from cells using an RNA isolation kit, the concentration and purity of RNA samples were determined using a NanoDrop spectrophotometer, cDNA was synthesized using a PrimeScript RTreagent Kit and gDNA Eraser, and gene expression levels were analyzed using TB Green Premix Ex Taq II. -ΔΔCT The method was used to calculate the relative expression of the target gene and normalized it to the expression of β-actin.
[0103] The results are as follows Figure 5 As shown in BD, after 7 days, the expression levels of Acan, Col2a1 and Sox9 genes in the Fe2O3 group were higher than those in the blank group and CeO2 group, indicating that Fe2O3 has the ability to promote the chondrogenic differentiation of BMSCs; at the same time, the expression of the three marker genes in the CSH-CeO2-Fe2O3 group and CSH-CeO2-pFe2O3 group was significantly higher than that in the Fe2O3 group. After 14 days of culture, the expression levels of Acan, Col2a1 and Sox9 genes in the CSH-CeO2-pFe2O3 group were significantly higher than those in the other groups. The results showed that the logically released Fe2O3 nanoparticles in the CSH-CeO2-pFe2O3 hydrogel significantly promoted the chondrogenic differentiation of BMSCs.
[0104] Example 13 Anti-inflammatory effect of CSH-CeO2-pFe2O3 hydrogel
[0105] (1) 100 μL of a solution with a density of 2×10 5 cells / mL of RAW 264.7 cells were placed in a 0.4 mmol L -1 The cells were cultured in a laser confocal culture dish (Φ15 mm) containing H2O2 solution for 1 day. Then, the culture medium was removed, and CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 were added to the four experimental groups, and fresh DMEM culture medium was added to the blank group. After 4 days of culture, live / dead cells were stained with calcein-AM and propidium iodide for 30 minutes at 37°C. Finally, fluorescence images were collected using a laser confocal microscope.
[0106] The results are as follows Figure 6As shown in A, after 4 days of culture, the number of surviving cells in the CeO2 group was significantly higher than that in the blank group and the Fe2O3 group, and the number of dead cells was relatively small, indicating that CeO2 nanoparticles have good antioxidant effects. Compared with the CeO2 group, the Fe2O3 group and the CSH-CeO2-Fe2O3 group, the CSH-CeO2-pFe2O3 group had the highest number of surviving cells and the lowest number of dead cells. The results showed that the CSH-CeO2-pFe2O3 hydrogel had a significant anti-inflammatory effect.
[0107] (2) Add 1 mL of a 1×10 5 RAW264.7 cells with a concentration of 10 μg / mL were induced with LPS (10 μg / mL) for 24 hours. Subsequently, the blank group was replaced with fresh DMEM medium, and the three experimental groups were added with medium containing CeO2, Fe2O3, CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3, respectively. After 3 and 7 days of culture, total RNA was extracted from the cells using an RNA isolation kit, the concentration and purity of the RNA samples were determined by a NanoDrop spectrophotometer, cDNA was synthesized by a PrimeScript RTreagent Kit and gDNA Eraser, and gene expression levels were analyzed by TB Green Premix Ex Taq II. -ΔΔCT The method was used to calculate the relative expression of the target gene and normalized it to the expression of β-actin.
[0108] The experimental results are as follows Figure 6 As shown in BE, after 3 days of culture, the gene expression of the anti-inflammatory cytokine IL-10 in the CeO2 group, CSH-CeO2-Fe2O3 group and CSH-CeO2-pFe2O3 group was significantly upregulated, while the gene expression of pro-inflammatory cytokines (IL-18, IL-1β and TNF-α) was significantly downregulated compared with the blank group and Fe2O3 group. After 7 days of culture, compared with the CeO2 group, the gene expression of the anti-inflammatory cytokine IL-10 in the CSH-CeO2-Fe2O3 group and CSH-CeO2-pFe2O3 group continued to be upregulated, while the expression of pro-inflammatory cytokines (IL-18, IL-1β and TNF-α) continued to be downregulated. The results show that CSH-CeO2-pFe2O3 hydrogel can continuously promote the expression of anti-inflammatory factors and inhibit the expression of pro-inflammatory factors in RAW264.7 cells.
[0109] (3) 1 mL of density is 1×10 4cells / mL of RAW 264.7 cell suspension was seeded on glass coverslips in 24-well plates. After 12 hours of culture, 100 ng / mL LPS was added to each well to stimulate RAW264.7 cells for 24 hours. Then, the culture medium was replaced with complete culture medium containing CeO2, Fe2O3, CSH-CeO2-Fe2O3, and CSH-CeO2-pFe2O3 and cultured for 4 days. After rinsing with PBS, the primary antibody for IL-1β was added and incubated at 4°C overnight. After washing with PBS, the secondary antibody was added and incubated again for 1 hour. Finally, immunofluorescence images were obtained using a fluorescence microscope.
[0110] The results are as follows Figure 6 As shown in Figure F, the fluorescence intensity of the CSH-CeO2-pFe2O3 group was significantly weakened compared with the other groups. The results showed that the CSH-CeO2-pFe2O3 hydrogel enhanced its anti-inflammatory properties through the controlled release of CeO2 nanoparticles.
[0111] (4) 1 mL of density is 1×10 4 cells / mL of RAW 264.7 cell suspension was seeded on glass coverslips in 24-well plates. After 12 hours of culture, 100 ng / mL LPS was added to each well to stimulate RAW264.7 cells for 24 hours. Then, the culture medium was replaced with complete culture medium containing CeO2, Fe2O3, CSH-CeO2-Fe2O3, and CSH-CeO2-pFe2O3 and cultured for 4 days. After rinsing with PBS, primary antibodies for CD86 and CD206 were added and incubated at 4°C overnight. After washing with PBS, secondary antibodies were added and incubated again for 1 hour. Finally, immunofluorescence images were acquired using a fluorescence microscope.
[0112] The results are as follows Figure 6 As shown in GH, compared with the blank group, Fe2O3 group, CeO2 group and CSH-CeO2-Fe2O3 group, the fluorescence intensity of CD86 in the CSH-CeO2-pFe2O3 group was significantly reduced, while the fluorescence intensity of CD203 was greatly increased. The results showed that CSH-CeO2-pFe2O3 hydrogel inhibited the pro-inflammatory (M1) phenotype of RAW 264.7 cells and promoted the anti-inflammatory (M2) phenotype of macrophages.
[0113] Example 14 Cartilage tissue regeneration of CSH-CeO2-pFe2O3 hydrogel
[0114] (1) SD rats (male, 250-300 g) were housed in a standard laboratory. Thirty rats were randomly divided into five groups (blank group, CeO2 group, Fe2O3 group, CSH-CeO2-Fe2O3 group, and CSH-CeO2-pFe2O3 group), with 6 rats in each group. Before surgery, the rats were anesthetized by intraperitoneal injection of 10% (w / v) sodium pentobarbital (0.3 mL / 100 g). After shaving and disinfecting the surgical site, the skin and muscle tissue covering the left knee of each rat were cut with a scalpel to expose the joint pulley site. A cylindrical cartilage defect with a diameter of 2 mm and a height of 1.5 mm was formed at the pulley site of the left knee of each rat using an electric drill. Subsequently, CeO2, Fe2O3, CSH-CeO2-Fe2O3, and CSH-CeO2-pFe2O3 samples were injected into the surgical site to completely fill the defect, except for the blank group. At 4 and 8 weeks after surgery, the rats were euthanized using an overdose of sodium pentobarbital, and samples were collected.
[0115] The experimental results are as follows Figure 7 As shown in AB, at 4 weeks after surgery, there was almost no new cartilage tissue in the defect site of the blank group; only a small amount of regenerated cartilage tissue was formed in the CeO2 and Fe2O3 groups; and the CSH-CeO2-pFe2O3 group had significant cartilage tissue regeneration. At 8 weeks after surgery, the surface of the new cartilage in the CSH-CeO2-pFe2O3 group was smooth and seamlessly integrated with the adjacent host tissue, which was significantly better than that of the CeO2, Fe2O3 and CSH-CeO2-Fe2O3 groups. The ICRS macroscopic score results were consistent with the gross morphological observation results.
[0116] (2) The collected specimens were fixed in 4% paraformaldehyde for 2 days and decalcified in 10% ethylenediaminetetraacetic acid solution for 7 days. Subsequently, the samples were dehydrated in alcohol gradients, embedded in paraffin, and cut into 6 μm slices. Finally, the tissue sections were stained with hematoxylin & eosin (H&E).
[0117] The experimental results are as follows Figure 7 C. After 4 weeks of implantation, obvious new cartilage tissue was observed in the CSH-CeO2-Fe2O3 and CSH-CeO2-pFe2O3 groups, and the regenerated tissue was significantly better than that in the CeO2 and Fe2O3 groups. After 8 weeks of implantation, CSH-CeO2-pFe2O3 presented transparent cartilage rich in mature chondrocytes and seamlessly integrated with the adjacent host cartilage, and the results were significantly better than those in the CeO2, Fe2O3 and CSH-CeO2-Fe2O3 groups. H&E staining results showed that CSH-CeO2-pFe2O3 hydrogel significantly promoted the regeneration of cartilage tissue.
[0118] (3) The fixed samples were decalcified in 10% ethylenediaminetetraacetic acid solution for 7 days, then dehydrated in alcohol gradient, embedded in paraffin, cut into 6 μm slices, and finally the tissue sections were Masson stained.
[0119] The experimental results are as follows Figure 7 D. At week 4, the blue staining area in the CSH-CeO2-pFe2O3 hydrogel group was significantly more than that in the CSH-CeO2-Fe2O3, Fe2O3, CeO2, and blank groups, indicating the formation of a large number of collagen fibers. At week 8, the CSH-CeO2-Fe2O3 group had more collagen fibers than the blank, CeO2, and Fe2O3 groups, and a large number of dense collagen fibers were formed in the CSH-CeO2-Fe2O3 group. The results of Masson staining showed that the CSH-CeO2-pFe2O3 hydrogel significantly accelerated the deposition process of collagen.
[0120] (4) The fixed samples were decalcified in 10% ethylenediaminetetraacetic acid solution for 7 days, then dehydrated in alcohol gradient, embedded in paraffin, cut into 6 μm slices, and finally the tissue sections were stained with Saf-O / FG.
[0121] The experimental results are as follows Figure 7 E. At 8 weeks after surgery, the CeO2 and Fe2O3 groups showed a small amount of red staining, indicating that a small amount of proteoglycan was secreted. In contrast, the proteoglycan content in the CSH-CeO2-Fe2O3 group increased significantly. The thickness of the new cartilage in the CSH-CeO2-pFe2O3 hydrogel group was similar to that of normal tissue, showing a large area of red staining. Saf-O / FG staining results showed that the CSH-CeO2-pFe2O3 hydrogel effectively increased the secretion of proteoglycan.
[0122] In summary, the present invention provides (1) a collagen hydrogel that logically releases cerium oxide nanoparticles and iron oxide nanoparticles, wherein the collagen hydrogel comprises a collagen substrate, and cerium oxide nanoparticles and iron oxide nanoparticles uniformly cross-linked on the collagen substrate, wherein the iron oxide nanoparticles are loaded in poly (D, L-lactic acid-co-glycolic acid) microspheres; (2) the collagen hydrogel has good mechanical strength, injectability and significant self-healing ability; (3) the collagen hydrogel can intelligently respond to high levels of ROS and achieve explosive release of cerium oxide nanoparticles and delayed and sustained release of iron oxide nanoparticles; (4) the collagen hydrogel can release cerium oxide nanoparticles in a continuous manner and release iron oxide nanoparticles in a continuous manner; and The white hydrogel has significant resistance to enzyme degradation and sustained antioxidant effect; (5) the collagen hydrogel has excellent biocompatibility and bioactivity, is non-cytotoxic, and can significantly promote cell proliferation, adhesion and cartilage differentiation of bone marrow mesenchymal stem cells; (6) the collagen hydrogel can effectively alleviate inflammatory response, inhibit the pro-inflammatory (M1) phenotype of macrophages and promote the anti-inflammatory (M2) phenotype, while upregulating the expression of anti-inflammatory factors and downregulating the expression of pro-inflammatory factors; (7) the collagen hydrogel can accelerate the deposition of collagen fibers and the secretion of proteoglycans, thereby significantly promoting cartilage tissue regeneration; (8) the collagen hydrogel can be used in the clinical treatment of osteoarthritis.
Claims
1. A collagen hydrogel that logically releases cerium oxide nanoparticles and iron oxide nanoparticles, characterized in that: The collagen hydrogel comprises a collagen substrate, and cerium oxide nanoparticles and iron oxide nanoparticles uniformly dispersed on the collagen substrate. The iron oxide nanoparticles are loaded in poly (D, L-lactic acid-co-glycolic acid) microspheres.
2. The collagen hydrogel according to claim 1, characterized in that The collagen is animal type I collagen.
3. The collagen hydrogel according to claim 2, characterized in that The collagen is thiol-modified yak type I collagen.
4. The method for preparing collagen hydrogel according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) Weighing thiol-modified type I collagen and dissolving it in acetic acid solution, stirring to obtain a solution with a final concentration of 5 mg / mL; (2) encapsulating the thiol-modified type I collagen solution obtained in step (1) into a dialysis bag and performing gradient dialysis until it becomes neutral; (3) 100 μL of 1 mM cerium oxide nanoparticle aqueous solution, 5 mg of iron oxide nanoparticles and 900 μL of thiol-modified yak type I collagen solution were mixed and allowed to stand at room temperature to obtain CSH-CeO2-pFe2O3 hydrogel.
5. Use of the collagen hydrogel according to any one of claims 1 to 3 in promoting bone / cartilage tissue regeneration.
6. Use of the collagen hydrogel according to any one of claims 1 to 3 in the preparation of a medicament for preventing and / or treating cartilage defects.
7. Use of the collagen hydrogel according to any one of claims 1 to 3 in the preparation of a medicament for preventing and / or treating arthritis.
8. The use according to claim 7, characterized in that The arthritis is infectious arthritis and / or non-infectious arthritis.
9. The use according to claim 8, characterized in that The non-infectious arthritis includes one or more of degenerative arthritis, rheumatoid arthritis, rheumatic arthritis, gouty arthritis and osteoarthritis.
Citation Information
Patent Citations
A preparation method of double cross-linked stem cell sphere hydrogel for osteoarthritis
CN113999404B
Injectable anti-inflammatory hydrogel for relieving osteoarthritis as well as preparation method and application of injectable anti-inflammatory hydrogel
CN116041967A